The Types of Extreme Tourism and Pilgrimage Tourism (Information Horizons: American Journal of Library and Information Science Innovation (2993-2777), 2024)
The article highlights some general aspects of Extreme tourism, this type of this tourism is an adventurous niche that involves exploring the most challenging and often dangerous environments on Earth. It's for thrill-seekers who crave experiences beyond the ordinary, from scaling icy peaks to diving with sharks. It's not just about the adrenaline rush; it's about testing limits and embracing the raw beauty of nature.